Training of future teachers for the implementation of continuity of pre-school and primary mathematical education - Syzdykbayeva, Aigul; Bagitovna, Kinzhibayeva Fariza; Bakirovna, Akpayeva Assel; Evgenievna, Ageyeva Larissa; Zhangazinovna, Mynzhassarova Marzhangul; Meirkhanovna, Baykulova Aigerim (Jurnal Cakrawala Pendidikan, 2022)
The article deals with the problem of the future teacher’s readiness to implement the continuity of preschool and primary mathematical education. The purpose of the study: to determine the level of training of future teachers to implement mathematical education and to summarize the data obtained during the pedagogical experiment. The standard curriculum of preschool education and training and the curriculum of the 1st grade are analyzed to determine the continuity of mathematical education. The authors developed a diagnostic program that allowed students to identify the level of readiness for the implementation of the continuity of math education. To gather objective information about the possibility of their further development, through the content of pedagogical subjects and elective course "Basics of continuity of preschool and elementary math education", as well as to identify ways to stimulate the desire of the interest of students to assimilate the necessary knowledge and skills in this field.